Formaldehyde: exposure and genotoxicity assessments and potential health effects - Ladeira, Carina (2015)
Worldwide formaldehyde is manipulated with diverse usage properties, since industrial purposes to health laboratory objectives, representing the economic importance of this chemical agent. Therefore, many people are exposed to formaldehyde environmentally and/or occupationally. Considering the latter, there was recommended occupational exposure limits based on threshold mechanisms, limit values and indoor guidelines. Formaldehyde is classified by the International Agency for Cancer Research (IARC) as carcinogenic to humans (group 1), since a wide range of epidemiological studies in occupational exposure settings have suggested possible links between the concentration and duration of exposure and elevated risks of nasopharyngeal cancer, and others cancers, and more recently, with leukemia. Although there are different classifications, such as U.S. EPA that classified formaldehyde as a B1 compound, probable human carcinogen under the conditions of unusually high or prolonged exposure, on basis of limited evidence in humans but with sufficient evidence in animals. Formaldehyde genotoxicity is well-known, being a direct-acting genotoxic compound positively associated for almost all genetic endpoints evaluated in bacteria, yeast, fungi, plants, insects, nematodes, and cultured mammalian cells. There are many human biomonitoring studies that associate formaldehyde occupational exposure to genomic instability, and consequently possible health effects. Besides the link with cancer, also other pathologies and symptoms are associated with formaldehyde exposure, namely respiratory disorders such as asthma, and allergic contact dermatitis. Nowadays, there are efforts to reduce formaldehyde exposure, namely indoor. Europe and United States developed more strict regulation regarding formaldehyde emissions from materials containing this agent. Despite the regulations and restrictions, formaldehyde still continues to be difficult to eliminate or substitute, being biomonitoring an important tool to control possible future health effects.